Chapter 7: Oyster Mushroom Flour and Its Composite Steamed Bun: Nutritional Quality, Physical Properties, and Sensory Accepta - Ho, Dr. Lee Hoon; Zulkifli, Dr. Noroul Asyikeen; Arumugam, Prof. Madya Dr. Nalini (Nova Science Publishers, 2018)
Oyster mushroom is an edible mushroom that gained popularity lately due to its good nutritional values. Proximate composition of grey and white oyster mushroom flour (GOMF and WOMF, respectively) were determined in the study. Then, composite steamed buns were prepared using either GOMF or WOMF. Wheat flour was partially substituted with GOMF or WOMF at 3 and 5% (w/w) to prepare 3GOM, 3WOM, 5GOM, and 5WOM, respectively. Steamed bun without GOMF and WOMF served as control. Prepared steamed buns were evaluated for the physical properties (i.e., water activity, weight, volume, specific volume, and texture profile), nutritional values (i.e., proximate composition, total starch, and resistant starch), and sensory attributes. The results showed significant difference (P < 0.05) in moisture, ash, crude protein, crude fat, total carbohydrate, and calorie contents between GOMF and WOMF. All the composite steamed buns indicated significantly higher (P < 0.05) ash, crude protein, crude fat, and crude fibre contents, but, significantly lower (P < 0.05) total carbohydrate content than that of the control steamed bun. Composite steamed buns resulted in a significant increase (P < 0.05) in resistant starch content. Composite steamed buns showed a significantly darker (P < 0.05) skin and crumb colour, significantly lower (P < 0.05) volume and specific volume, and significantly higher (P < 0.05) hardness values than that of the control steamed bun. Sensory evaluation indicated that the substitution of GOMF or WOMF for wheat flour at 3 and 5% levels, did not significantly affect (P > 0.05) the overall acceptability on steamed bun by sensory panellists. In general, partial substitution of either GOMF or WOMF for wheat flour could improve the nutritional quality of the steamed bun.